Effect of Superovulation on Piglet Production - Mege, RA; Manalu, W; Kusumorini, N; Nasution, SH (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2006)
Sixty gilts with average body weight of 107.80 + 5.10 kg were used in an experiment to study the use of PMSG and hCG as superovulation agent to increase piglet production. In this experiment 60 gilts were assigned into a completely randomized design with 4 treatments of superovulation with dose level 0, 600, 1200 and 1800 IU/gilt. Injections were conducted 3 days before estrus. During gestation, gilts were placed in single pigpen, and maintained to term. The parameters were birth weight, preweaning growth and mortality. The results showed that superovulation dose levels of 600 and 1200 IU/gilt increased the piglet birth weight, litter size, preweaning growth and piglet production at 90 days. It is concluded that superovulation with dose levels of 600 to 1200 IU can improve productivity. (Animal Production 8(1): 8-15 (2006)Â Key Words : Â Â Superovulation, gilts, piglet production